Impact on health care workers employed in high-risk areas during the Toronto SARS outbreak - Styra, Rima (J Psychosom Res, 2008)
BACKGROUND: A number of publications focusing on health care workers (HCWs) during a severe acute respiratory syndrome (SARS) outbreak have suggested that HCWs experienced psychological distress, particularly increased levels of posttraumatic stress symptomatology (PTSS). Factors contributing to increased distress in HCWs working in high-risk areas treating patients with SARS have not been fully elucidated. The goal of this study was to quantify the psychological effects of working in a high-risk unit during the SARS outbreak. METHODS: HCWs in a Toronto hospital who worked in high-risk areas completed a questionnaire regarding their attitude toward the SARS crisis along with the Impact of Event Scale—Revised, which screens for PTSS. The comparison group consisted of clinical units that had no contact with patients infected with SARS. RESULTS: Factors that were identified to cause distress in the 248 respondent HCWs were the following: (a) perception of risk to themselves, (b) impact of the SARS crisis on their work life, (c) depressive affect, and (d) working in a high-risk unit. In addition, HCWs who cared for only one SARS patient in comparison to those caring for multiple SARS patients experienced more PTSS. CONCLUSIONS: As expected, HCWs who were working in high-risk units experienced greater distress. Contrary to expectations, HCWs who experienced greater contact with SARS patients while working in the high-risk units were less distressed. This suggests that HCW experience in treating patients infected with SARS may be a mediating factor that could be amenable to intervention in future outbreaks.